The relation between the self-esteem levels and decision-making styles of the students doing sports and the students not doing sports in high schools - Özgür Gül; Hakan Salim Caglayan (Türk Spor ve Egzersiz Dergisi)
The objective of this study to determine the self-esteem levels and decision-making styles of the students studying at high schools according to their state of doing and not doing sports and to reveal whether there is a relation between their self-esteem levels and decision-making styles. The research group has been constituted by total  403 students,  114 of whom were doing sports and 289 not doing sports, studying at the high schools acting under Konya Provincial Education Directorate in the first half of the 2014-2015 school year. The group doing sports consisted of the students representing their schools and having taken part in competitions in different branches and the group not doing sports was constituted by the students studying in different departments of the same school and not active in a branch. In the study, as the data collection tool, “Coopersmith Self-esteem Inventory” developed by Coopersmith and adapted to Turkish by Turan amp; Tufan as well as “Decision-making Scale in Adolescents” developed by Mann et al. and adapted to Turkish by Çolakkadıoğlu were used. The fact that whether the data were distributed normally or not was scrutinized by the Kolmogorov-Smirnov test and following such scrutiny, as the data were distributed normally, Pearson moment correlation (r) coefficient technique was used to reveal the relation between the self-esteem levels and decision-making styles of students. α=0.05 was chosen as the significance level in the study. At the end of the study, it was determined that both the self-esteem levels and decision-making styles of the students doing sports were higher than those who do not do sports. It was ascertained in the students doing sports that there is a relation at moderate level and positive tendency between their self-esteem levels and self-respect in decision-making; at low level and negative tendency between their apathy and avoidance of responsibility decision-making styles, and at moderate level and negative tendency between their panic decision-making styles. In the students not doing sports, a relation at low level and positive tendency in their self-esteem levels and self-respect in decision-making and cautious-selectivity decision-making styles, and at low level and negative tendency between their panic and avoidance of responsibility decision-making styles, was determined.